PEMEROLEHAN BAHASA ANAK TUNAGRAHITA RINGAN USIA 10-17 TAHUN: STUDI KASUS DI SLB C AUTIS NEGERI TUBAN - Windhi Agus Tia Wika; Syamsul Ghufron; Laila Tri Lestari (Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to describe the acquisition of words, sentences, and meanings of mildly mentally retarded children aged 10-17 years at SLB C Autism State Tuban. This research method is descriptive qualitative. Data collection techniques using observation, interview, recording, transcription, and note-taking techniques. The results of this study reveal that mildly mentally retarded children aged 10-17 years master the types of nouns, verbs, adjectives, numerals, pronouns, adverbs, prepositions, and conjunctions. Types of verb sentences, basic sentences, and sentence transformations of the process of elimination and addition. Mastery of meaning that is able to conceptualize meaning based on the field of meaning and distinguishing features of meaning.